Upaya peningkatan pemahaman konsep dan keterampilan kolaborasi peserta didik melalui implementasi PBL berbasis lesson study - Rahmawati, Jevi Milda; Anggraini, Atika; Nurcahyo, Ima Agung (2023)
Understanding concepts and collaboration skills are important things that are mastered and needed by students, as mandated by the 2013 curriculum. The application of this curriculum emphasizes the output of students who are able to contribute knowledgebased skills in the community environment later. This study aims to improve the understanding of concepts and collaboration skills of class XI IPS 2 students through the implementation of lesson study-based PBL. This type of research is descriptive classroom action research (PTK). The population in this study were all students of class XI IPS. The sample in this study were students of class XI, IPS 2, who were selected using a purposive sampling technique. The results of this study indicate that the implementation of lesson study-based PBL can improve the conceptual understanding and collaboration skills of class XI IPS 2 students in the material on the reproductive system. The average value of understanding the concept from cycles 1 to 3 is 31.47; 55.29; and 72.94. The average values of collaboration skills from cycles 1 to 3 are: 1) contribution indicators (2.05; 2.41; 2.76), 2) time management indicators (1.91; 2.21; 2.26), 3) problem solving indicators (2; 2.26; 2.26), 4) indicators of working with other people (1.91; 2.21; 2.32), 5) indicators of investigative techniques (1.94; 2.1; 2,26).